Risk Stratification Tools in Predicting Survival and Transformation of Therapy-Related Myelodysplastic Syndrome: A Systematic Review - Siti Rubiyat; Bernadetha kusuma kris firmantya tei seran; Albert Tri Rustamadji (Jurnal Kedokteran Diponegoro (Diponegoro Medical Journal), 2024)
Background: Therapy-related myelodysplastic syndromes (t-MDS) are grouped with therapy-related acute lymphoblastic leukemia (t-ALL) and therapy-related myelodysplastic/myeloproliferative neoplasms (t-MDS/MPN) under therapy-related myeloid neoplasms (t-MNs). Most myelodysplastic syndrome (MDS) prognostic models have excluded t-MDS patients, leaving their prognostic utility uncertain. Objective: This systematic review aims to synthesize the predictive utility of existing and novel risk stratification tools in assessing the survival and transformation of t-MDS. Methods: Searches were conducted in PubMed and ScienceDirect following PRISMA 2020 guidelines, focusing on overall survival and transforming t-MDS into acute myeloid leukemia (AML). Two reviewers independently screened references, extracted data, and assessed quality using the QUAPAS-2 tool. Results: From 1715 abstracts and 13 papers, 6 studies were included. Three studies on the International Prognostic Scoring System (IPSS) showed significant predictive power for survival and AML transformation. Five studies on the revised IPSS (IPSS-R) and WHO-based Prognostic Scoring System-revised (WPSS-R) also showed significant results. One study highlighted the cytogenetic component of IPSS-R (cIPSS-R) as highly prognostic. Conclusion: Existing and novel risk stratification tools demonstrate significant prognostic power for t- MDS. Further refinement and validation are needed to enhance risk assessment and treatment strategies.